2003
DOI: 10.1007/s11664-003-0091-5
|View full text |Cite
|
Sign up to set email alerts
|

Properties of Bi-doped PbTe layers grown by liquid phase epitaxy under controlled Te vapor pressure

Abstract: Effects of Bi doping in PbTe liquid-phase epitaxial layers grown by the temperature difference method under controlled vapor pressure (TDM-CVP) are investigated. For Bi concentrations in the solution, x Bi , lower than 0.2 at.%, an excess deep-donor level (activation energy E d Ϸ 0.03-0.04 eV) appears, and Hall mobility is low. In contrast, for x Bi Ͼ 0.2 at.%, Hall mobility becomes very high, while carrier concentration is in the range of 10 17 cm Ϫ3 . Inductive coupled plasma (ICP) emission analysis shows th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
8
0

Year Published

2003
2003
2017
2017

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 10 publications
0
8
0
Order By: Relevance
“…The reverse bias is 1.0 V. From the straight line portion of the graph, the activation energy of the dark current was obtained as 0.067 eV. This deep level energy was not revealed in Hall Effect measurements of heavily Bi-doped epitaxial layers in our previous study [5]. Therefore we assumed that the deep level is sourced from the PbTe p-n junction; in particular, from the Tl-doped p-side layer.…”
Section: Methodsmentioning
confidence: 94%
See 3 more Smart Citations
“…The reverse bias is 1.0 V. From the straight line portion of the graph, the activation energy of the dark current was obtained as 0.067 eV. This deep level energy was not revealed in Hall Effect measurements of heavily Bi-doped epitaxial layers in our previous study [5]. Therefore we assumed that the deep level is sourced from the PbTe p-n junction; in particular, from the Tl-doped p-side layer.…”
Section: Methodsmentioning
confidence: 94%
“…The photocurrent density of the heavily Bi-doped sample is approximately 20 times and 3 times greater than that of the undoped sample and heavily In-doped sample, respectively. Since PbTe systems are characterized by a high electric constant (e = 1400-1800) [11], we previously assumed that the high Bi concentration induced strong self-compensation, reducing the number of free electrons and the wide depletion layer [4,5]. Moreover, the free electrons in the n-type layer absorb less infrared radiation in heavily Bi-doped materials than in the other evaluated materials.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…6 From these results, it is suggested that at high Bi concentration, a Bi-donor atom located at the Pb site and a Bi-acceptor atom make a nearestneighbor or very near donor-acceptor (DA) pair, which does not cause effective ionic scattering nor form a deep level. Also, Bi impurities form deep levels with E d ϭ 0.06Ϫ0.08 eV, only at a relatively low Biconcentration region, i.e., x Bi Ͻ 0.2 at.%, or, for Te vapor pressure exceeding the optimum value for stoichiometry.…”
mentioning
confidence: 99%